2018
DOI: 10.1007/s00592-018-1114-2
|View full text |Cite|
|
Sign up to set email alerts
|

Two-hour post-challenge glucose is a better predictor of adverse outcome after myocardial infarction than fasting or admission glucose in patients without diabetes

Abstract: AGT is under-diagnosed on current guidelines. 2h-PG is a better predictor of prognosis compared to APG and FPG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 64 publications
0
16
1
Order By: Relevance
“…whereas each 1 mmol/L increase in FPG was associated with higher risk of MACE (28%) and cardiovascular mortality (51%) among post MI patients in UK; the risks however, were not significant in the models including both FPG and 2 h-PCPG [28]. The finding of the current study showed that each 1.04 mmol/L increase in FPG was associated with 16% and 17% higher risk of CVD and CHD, respectively.…”
Section: Discussioncontrasting
confidence: 60%
“…whereas each 1 mmol/L increase in FPG was associated with higher risk of MACE (28%) and cardiovascular mortality (51%) among post MI patients in UK; the risks however, were not significant in the models including both FPG and 2 h-PCPG [28]. The finding of the current study showed that each 1.04 mmol/L increase in FPG was associated with 16% and 17% higher risk of CVD and CHD, respectively.…”
Section: Discussioncontrasting
confidence: 60%
“…3,14 We have reported that 2h-PG was a better determinant of post-MI prognosis than FPG or APG. 13,21 In the EUORASPIRE IV 20 and Silent Diabetes Study, 27 2h-PG, but not FPG or HbA1c, was related to prognosis. The 2h-PG, but not the FPG, was associated with adverse post-MI prognosis in patients with pDM in this.…”
Section: Discussionmentioning
confidence: 97%
“…22 These tests under-diagnose dysglycaemia. 13 Undiagnosed pDM could add to the already high prognostic risk of this population and would affect the advice given to these patients. Thus, we wanted to explore whether (1) fasting and/or post-load hyperglycaemia below the threshold of DM affected post-MI prognosis, (2) FPG alone could identify this risk and (3) 2h-PG added any prognostic risk over and above FPG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is accumulating that it is more important to find out whether CAD patients have dysglycaemia, defined as either IGT or T2DM, than to classify them as having either IGT or T2DM. 11,170 The latter is an arbitrary division that was introduced to distinguish people with dysglycaemia who had T2DM from those who ran a high risk of developing T2DM. 171 The present study adds new information by incorporating hospitalisation for heart failure in the primary endpoint, which traditionally only includes cardiovascular death, non-fatal MI and stroke.…”
Section: Prognostic Implications Of Indicators Of Dysglycaemiamentioning
confidence: 99%